Effect of Sciatic Nerve Mobilization with Combination Therapy on Myofascial Trigger Points in a Young Obese Female with Piriformis Syndrome - A Case Report (International Journal of Physiotherapy, 2025)
Background: Piriformis syndrome (PS), which contributes to 0.3% to 6% of low back pain and sciatica cases, affects approximately 2.4 million individuals annually out of the 40 million yearly instances of these conditions. This syndrome is primarily observed in middle-aged adults, with a notable prevalence among young obese females. It is characterized by unilateral gluteal pain extending down the leg, muscle weakness, and numbness. Given the variable efficacy of current treatments, this study aims to investigate the potential benefits of combination therapy—specifically, ultrasound (US) and interferential therapy (IFT)—as well as sciatic nerve mobilization in managing PS in young obese adult females.Case Summary: A 35-year-old obese female presented with chief complaints of pain in walking, lower back, and right buttock for the past 15 days. The pain worsened with all activities of daily living. Clinical examination revealed marked tenderness and weakness in the right piriformis muscle, accompanied by restricted hip abduction and internal rotation. Functional limitations included difficulty with prolonged sitting, walking, and stair climbing. Diagnostic tests confirmed PS with positive piriformis, Freiberg, and PACE sign. The patient was given a combination of therapy and sciatic nerve mobilization as physiotherapeutic treatment.Outcome Measures: The outcomes were reported on the Numerical Pain rating scale, Manual muscle testing, WHO-5 quality index, and Barthel Index.Conclusion: This study highlights the effectiveness of combination therapy and sciatic nerve mobilization in managing PS.